Physical Fitness and Physical Activity of Students at Elementary School Country 2 Dangdeur - Fabiyan Fahliyansyah; Sumbara Hambali; Veny Juniarni Hardi (Journal of Physical and Outdoor Education, 2026)
This study aims to determine the level of physical fitness and physical activity among students at SDN 2 Dangdeur. The research method used is descriptive quantitative with a survey technique. The population and sample consisted of 74 students (38 boys and 36 girls), selected using total sampling. The instrument used to measure physical fitness was the Indonesian Student Fitness Test (TKSI) Phase C, while physical activity was assessed using a modified daily activity questionnaire tailored to elementary school students. The results showed that most boys had a Moderate level of physical fitness (65.8%), followed by Good (15.8%), Poor (15.8%), and Very Poor (2.6%). Meanwhile, most girls were in the Poor category (63.9%), followed by Moderate (33.3%) and Very Poor (2.8%). In terms of daily physical activity, boys were generally quite active, with 13.2% categorized as Less Active, 65.8% as Moderately Active, and 21.1% as Very Active. Girls were also quite active, with 13.9% in the Less Active category, 66.7% Moderately Active, and 19.4% Very Active. These results indicate that boys have higher levels of physical fitness and activity compared to girls. The findings highlight the need for structured physical activity programs in schools to optimally support students' physical fitness.